Factors that Influence Consumer Buying Behaviour towards Hair Removal Cream; Evidence from Malaysian Females - Low, Sum Chween (2016)
The purpose of this study is to understand the influence of consumer buying intention towards hair removal cream in Malaysia. In view of the objectives, there are limitation in literature concerning consumer buying intention in consuming hair removal cream, especially in understanding the recent low demand in depilatory industry globally. With that being said, the available literature on hair removal cream buying behaviour does not address the current phenomenon. As such, it is important for the research being conducted in Malaysia. To further understand the phenomenon, the used of independent variable such as acceptability, affordability, accessibility and awareness is to be tested to derive the relationship of the consumer buying intention towards hair removal cream. As such, the use of grounded theory such as theory of reasoned action will be used as a guide to better understand the buying behaviour and intention of the participants. The research methodology use will be that of a correlation in nature and the result expected will be there is a positive relationship on the independent variables towards the buying intention of the consumers.